Evaluation of Learning through Work Practices Industry Program at University with the CIPP Model Approach - Rachmaniar, Rachmaniar; Yahya, Muhammad; Lamada, Mustari (International Journal of Environment, Engineering & Education, 2021)
Evaluation in a program is an important series that intends to evaluate the implementation of industrial practices. This study is an evaluation study with the CIPP evaluation model developed by Stufflebeam, analyzed quantitatively. Respondents in this study consisted of 5 Head of Department, 27 supervisors, 20 industrial supervisors, and 134 students who had carried out industrial practice class 2017. The results showed that 1) the context aspect had obtained categories according to the average value of 131.02. Significant in the context evaluation is that in the management of information systems supervisor respondents, the category is less following the percentage of 37.03 percent, so information systems need to be developed. 2) the input aspect in industrial practice management is in the category according to the average value of 57.08, which indicates the readiness of the management and students is appropriate, 3) the process aspect is in the category according to the average of 93.84. The category is not suitable for the role of supervisors who need improvement in student services and adequate guidance so that students can be directed, 4) product aspects with an average score of 85.30; this is shown by the changes that occur by students from personality, responsibility, and skill improvement.